Productivity-enhancing manufacturing clusters: Evidence from Vietnam - Emma Howard; Carol Newman; John Rand; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper we explore the extent to which firms experience productivity spillovers from clustering using a rich data source from Vietnam for 2002 to 2007, a period of significant transition. We address issues of simultaneity, self-selection and endogenous location choice of firms in an estimation of firm level productivity. Controlling for competition effects and distinguishing between urbanization and localization economies, we find strong evidence for productivity spillovers from clustering. The effects of these spillovers are found to be particularly large for foreign-owned firms. Our results provide support for spatial clustering policies in developing countries aimed at attracting foreign investment.
Keywords: D2; L2; L6; O1; 330; clustering; productivity; endogenous location choice; spillovers; Vietnam